Role of Security Forces in Disaster Management with references to Nepalese Security Forces - Upreti, Yukesh (Patan Pragya, 2022)
This article is based on the role of security forces in disaster management with references to Nepalese security forces Disasters are the serious disruption of the functioning of community or society. Nepal is a country highly vulnerable to natural disasters having a crucial effect on human life. There is an international practice to call out security forces in catastrophic situation for risk management. Nepalese society is highly dependent towards Security forces in the time of disasters. The study seeks to assess the role played by Nepalese security force in managing the disasters. The study follows qualitative approach with descriptive in nature to find out desired objective. Both primary and secondary data have contributed to find out the role of Nepalese security forces in disaster response and preparedness. The findings shows Nepalese security forces have demonstrated their skill and knowledge to counter both natural and man-made disasters to save life of people. The role is discussed in three phase i.e. Pre-disasters, during disasters and After Disasters. It shows that security forces are mostly concentrated in Search and rescue activity. Managing Disasters are multi-sectored work with collaborative efforts. The research stressed investing in Security forces for training and developing in order to build a capable rescuer. It is necessary for government of Nepal to take appropriate steps for job specialization in search and rescue in order to motivate and complement security forces. Also, a clear goal, vision, guidance and coordination within all sectors should be amplified.